Predictors of Dental caries among children 7-14 years old in Northwest Ethiopia: a community based cross-sectional study - Ayele Fenta A; Taye Belaynew W; Ayele Tadesse A; Gelaye Kassahun A (BMC, 2013)
Abstract Background Dental caries in children remains a significant public health problem. It is a disease with multifactorial causes. The aim of the study was to assess the prevalence and associated factors of dental caries among children between 7 to 14 years old. Methods A community based cross-sectional study was conducted in Gondar town from June 2011 to September 2011. A total of 842 children were involved in the study. Multi-stage sampling technique was used to select the children. Pretested and structured questionnaires were used to collect data from mothers. Clinical examination of children was done using dental caries criteria set by world health organization. Data were entered, cleaned and edited using EPI Info version 3.5.1 and exported to SPSS version 16.0 for analysis. Binary multiple logistic regression analyses was applied to test the association. Results Four hundred sixty three (55%) children were females. The prevalence of dental caries was 306(36.3%).The educational status of children's father (AOR=0.3, 95%CI, 0.17, 0.80), monthly household income (AOR=0.59, 95%CI, 0.01, 0.45), regular teeth brushing (AOR=0.08, 95% CI, 0.03, 0.20) and using mouth rinsing (AOR=0.40, 95% CI, 0.2, 0.80) were found statistically significantly associated with dental caries. Conclusions Dental caries were high among children in Gondar town. Low socioeconomic status and poor oral hygiene practices were the influencing factors for dental caries. Oral hygiene, dietary habits and access to dental care services are supreme important for the prevention of the problem.